A multidimensional approach to the analysis of perceived value in tourism - Topalović, Snežana; Marinković, Veljko (Hotel and Tourism Management, 2020)
The key to achieving business goals is based on both understanding and comprehending how consumers perceive a service offering and exploring the elements that determine customer satisfaction and loyalty. Modern tourism enterprises should focus on creating and delivering value to their consumers as a significant source of competitive advantage. The aim of this paper is to identify the dimensions of the service offer values of the travel agencies in which there are significant differences in the ratings of the female and male respondents. To meet the research objectives, a t-test for two independent samples was used. Field research was conducted and primary data were collected by the survey method. This paper seeks to show that value for service users is a complex and multidimensional concept. Tourism services can be better perceived and understood if they are analysed through a multidimensional approach to value, as users of tourism services can at the same time experience and enjoy functional, social, emotional and other factors. The paper presents different approaches to the analysis of perceived value that are present in the world marketing literature and which form the basis for conception of future research.